Hak Mantan Narapidana untuk Turut Serta dalam Pemerintahan - Noer Sida (Justitia et Pax, 2018)
AbstractThe general election is a means of implementing the people's sovereignty to elect people who will occupy the seat of government. This general election was held to realize a democratic country, where the leaders were chosen based on the majority of votes. Countries that adhere to democracy generally accommodate the political rights of their citizens in an election, whether they are direct or indirect. Basically everyone has the right to participate in government in other words everyone has the right to be elected or elected. Regarding to Election Commission Regulation Number 20 Year 2018 regarding the Nomination of Members of The House Representatives, Assembly at Provincial and Assembly at Regional, there is one requirement for legislative candidate became controversial because there is a prohibition on ex-prisoners of corruption, drugs (as a dealer), and sexual crimes against children to be the Nomination of Members of The House Representatives, Assembly at Provincial and Assembly at Regional. Some ex-convicts already did judicial review, therefore we need to understand the legality of the regulation for ex-convicts regarding to election.Key Words: Human Rights, Right to Participate in Government, Ex-convictAbstrakPemilihan umum adalah adalah sarana pelaksanaan kedaulatan rakyat untuk memilih orang-orang yang akan menduduki kursi pemerintahan. Pemilihan umum ini diadakan untuk mewujudkan negara yang demokrasi, di mana para pemimpinnya dipilih berdasarkan suara mayoritas terbanyak. Negara-negara yang menganut demokrasi, pada umumnya mengakomodir hak politik warga negaranya dalam suatu penyelenggaraan pemilihan umum, baik itu bersifat langsung maupun tidak langsung. Pada dasarnya setiap orang memiliki hak untuk berpartisipasi dalam pemerintahan dengan kata lain setiap orang memiliki hak untuk dipilih maupun memilih. Peraturan KPU Nomor 20 Tahun 2018 tentang Pencalonan Anggota DPR, DPRD Provinsi dan DPRD Kabupaten/Kota memberikan batasan satu syarat bagi calon anggota legislatif yang menjadi kontroversi karena adanya larangan bagi mantan narapidana  korupsi, narkoba (sebagai bandar), dan kejahatan seksual terhadap anak untuk mencalonkan diri sebagai anggota DPR, DPRD Provinsi dan DPRD Kabupaten/Kota. Beberapa pihak yang merasa dirugikan oleh peraturan tersebut mengajukan judicial review, oleh karena itu, patut dikaji bagaimana legalitas hak yang dimiliki oleh mantan narapidana dalam pemilihan umum.Kata Kunci: Hak Asasi Manusia, Hak untuk Turut Serta dalam Pemerintahan, Mantan Narapidana.